Expression of IL-17A in human atherosclerotic lesions is associated with increased inflammation and plaque vulnerability - Erbel, Christian; Dengler, Thomas; Wangler, Susanne; Lasitschka, Felix; Bea, Florian; Wambsganss, Nadine; Hakimi, Maani; Böckler, Dittmar; Katus, Hugo; Gleißner, Christian A. (Basic research in cardiology, 2011)
A chronic (auto)immune response is the critical mechanism in atherosclerosis. Interleukin-17A is a pivotal effector cytokine, which modulates immune cell trafficking and initiates inflammation in (auto)immune and infectious diseases. However, expression of IL-17A in the context of human atherosclerosis has hardly been explored. Carotid artery plaques were collected from 79 patients undergoing endarterectomy. Patients were grouped according to their symptomatic status (TIA, stroke), plaque morphology and medication. Quantitative RT-PCR was used to analyze tissue inflammation and immunohistochemistry to assess cellular source of IL-17A expression and lesion morphology. Carotid plaques from patients with ischemic symptoms were characterized by a highly activated inflammatory milieu including accumulation of T cells (p = 0.04) and expression of IL-6 and VCAM1 (p = 0.02, 0.01). Expression of IL-17A and its positive regulators IL-21 and IL-23 was present in atherosclerotic lesions, significantly upregulated in atheromas of symptomatic patients (p = 0.005, 0.004, 0.03), and expression of IL-17A and IL-21 showed a strong correlation (p = 0.002, r = 0.52). The cellular sources of lesional IL-17A expression are T cells, macrophages, B cells and plasma cells. Vulnerable/ruptured (complicated) plaques were significantly associated with IL-17A expression levels (p = 0.003). In addition, IL-17A showed a marked negative correlation with the potent anti-inflammatory/atheroprotective cytokine IL-10 (p = 0.0006, r = −0.46). Furthermore, treatment with a HMG-CoA reductase inhibitor or acetylsalicylic acid showed reduced levels of IL-21, IL-23 and VCAM1 (all p < 0.05), but did not influence IL-17A. The association of IL-17A with ischemic symptoms and vulnerable plaque characteristics suggests that the pro-inflammatory cytokine IL-17A may contribute to atherosclerosis und plaque instability.
Published: 01 December 2010
Gesehen am 29.04.2022